Ovarian Embryonal Carcinoma in a Dog. Issue 4 (November 2017) - Banco, B.; Ferrari, R.; Stefanello, D.; Groppetti, D.; Pecile, A.; Faverzani, S.; Longo, M.; Zani, D.D.; Ravasio, G.; Caniatti, M.; Grieco, V.
Summary: A 17-month-old female doberman pinscher was referred for an abdominal mass and ascites. Exploratory laparotomy revealed the presence of a large neoplastic mass replacing the right ovary and associated with multiple mesovarian, mesometrial and peritoneal nodules. An ovariohysterectomy was performed. Grossly, the tumour was soft and multilocular with large areas of haemorrhage and necrosis. Microscopically, it was infiltrative and composed of round and polygonal cells arranged respectively in solid sheets or forming distorted tubular structures separated by thick fibrovascular septae. Tubules contained necrotic debris, proteinaceous fluid or small endoluminal papillary structures. Marked cellular atypia, multiple neoplastic emboli and high mitotic count were observed. Immunohistochemically, the round cells uniformly expressed placental alkaline phosphatase, while the polygonal cells arranged in tubules and papillae expressed cytokeratin (CK) AE1/AE3 and CK7. A final diagnosis of metastasizing ovarian embryonal carcinoma (EC), a primitive germ cell tumour characterized by rudimentary epithelial differentiation was made. Canine ovarian EC should be considered as a differential diagnosis for undifferentiated aggressive ovarian tumours in young dogs.